Synthesis and Characterization of Aluminosilicate Catalysts from Volcano Mud for Biofuel Production with Different Feedstocks - Hartati, Hartati; A'yuni, Qurrota; Dewi, Nita Safira; Firda, Putri Bintang Dea; Izzah, Adiba Naila; Prasetyoko, Didik; Harmami, Harmami; Ahmad, Shahrul Nizam (Indonesian Journal of Chemistry, 2024)
The increasing awareness of sustainable development goals has led to the intensive development of biofuel as a substitute for fossil fuels. This study investigates the potency of volcano mud (VM) as the precursor in synthesizing aluminosilicate catalysts for biofuel production. Three catalysts were synthesized, A3, A3T, and A5, in a manner to investigate the effect of tetrapropylammonium hydroxide (TPAOH) addition and hydrothermal time on the crystallinity, Si/Al ratio, and textural properties of the catalysts. The catalytic activity of the synthesized catalysts was evaluated in two different qualities of feedstock, i.e., oleic acid (OA) and waste cooking oil (WCO). It is found that A5 which is synthesized with longer hydrothermal of 5 h has desirable properties, a high mesoporous surface area of 159 m2/g, and a high acidity of 0.263 mmol/g. Catalyst A5 is proven to have similarly high catalytic activity in both WCO and OA feedstock, achieving a liquid yield of 93% with FAME selectivity of 95% for WCO and 95% liquid yield and FAME selectivity of 99% for OA feedstock. These results suggest that A5 is a versatile catalyst in biofuel production from either high or low-quality feedstocks.